Robust uniform stability criteria for fractional‐order gene regulatory networks with leakage delays. (25th March 2022) - Arjunan, Mani Mallika; Anbalagan, Pratap; Al‐Mdallal, Qasem
Abstract : In this paper, we aim to establish the uniform stability criteria for fractional‐order time‐delayed gene regulatory networks with leakage delays (FOTDGRNL). First, we establish the existence and uniqueness of the considered systems by using the Banach fixed point theorem. Second, the delay‐dependent uniform stability and robust uniform stability of FOFGRNLT are investigated with the help of certain analysis techniques depending on equivalent norm techniques. Finally, the paper comes up with two numerical examples to justify the applicability of our theoretical results.